Ionic Polyimide Derived Porous Carbon Nanosheets as High‐Efficiency Oxygen Reduction Catalysts for Zn–Air Batteries. Issue 29 (28th January 2020) - Tu, Kejun; Zou, Lingyi; Yang, Chongqing; Su, Yuezeng; Lu, Chenbao; Zhu, Jinhui; Zhang, Fan; Ke, Changchun; Zhuang, Xiaodong
Abstract: Two‐dimensional (2D) porous carbon nanosheets (2DPCs) have attracted great attention for their good porosity and long‐distance conductivity. Factors such as templates, precursors, and carbonization–activation methods, directly determine their performance. However, rational design and preparation of porous carbon materials with controlled 2D morphology and heteroatom dopants remains a challenge. Therefore, an ionic polyimide with both sp 2 ‐ and sp 3 ‐hybridized nitrogen atoms was prepared as a precursor for fabricating N‐doped hexagonal porous carbon nanosheets through a hard‐template approach. Because of the large surface area and efficient charge‐mass transport, the resulting activated 2D porous carbon nanosheets (2DPCs‐a) displayed promising electrocatalytic properties for oxygen reduction reaction (ORR) in alkaline and acidic media, such as ultralow half‐wave potential (0.83 vs. 0.84 V of Pt/C) and superior limiting current density (5.42 vs. 5.14 mA cm −2 of Pt/C). As air cathodes in Zn–air batteries, the as‐developed 2DPCs‐a exhibited long stability and high capacity (up to 614 mA h g −1 ), which are both higher than those of commercial Pt/C. This work provides a convenient method for controllable and scalable 2DPCs fabrication as well as new opportunities to develop high‐efficiency electrocatalysts for ORR and Zn–air batteries. Abstract : Two‐dimensional porous carbon nanosheets (2DPCs) with controlled hexagonal morphology and uniform nitrogen dopants were prepared by using ionic polyimide as the precursor. The activated 2DPCs (2DPCs‐a) exhibited promising oxygen reduction reaction (ORR) performance in alkaline and acidic media. As air cathode in Zn–air batteries, the 2DPCs‐a‐based batteries showed long stability and high capacity up to 614 mA h g −1 . The morphology and chemical composition of the as‐prepared 2DPCs‐a were stable after a long‐term stability measurement.